ENDE LOCAL HISTORY AS A CONTEXTUAL LEARNING RESOURCE FOR DEVELOPING HISTORICAL THINKING IN HISTORY EDUCATION: A LITERATURE REVIEW - Fatma Wati; Fahzalia R. Maysa (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
History education should not be limited to the transmission of factual knowledge but should encourage students to develop the ability to understand, analyze, and interpret the past through historical reasoning. This study aims to analyze the utilization of Ende local history as a contextual learning resource for developing historical thinking in history education. This research employs a literature review method using a conceptual synthesis approach. Data sources consist of 26 selected academic publications, including journal articles, books, and proceedings related to historical thinking, history education, local history, and cultural heritage of Ende.Literature selection was conducted through identification, screening, eligibility assessment, and data extraction processes. The collected data were analyzed using content analysis and thematic analysis to identify patterns and conceptual relationships among the reviewed studies. The findings indicate that Ende possesses diverse local historical sources, including colonial heritage sites, national historical sites, traditional villages, traditional architecture, oral traditions, and cultural rituals. These sources have significant potential as contextual learning resources because they provide authentic historical evidence that can support students in developing historical thinking. The synthesis shows that the utilization of Ende local history can facilitate students’ abilities to analyze historical evidence, understand historical perspectives, recognize continuity and change, and interpret historical significance. Therefore, local history can function not only as cultural heritage but also as an educational medium that transforms history learning into an inquiry-based and meaningful process.